2009
DOI: 10.1007/s11157-009-9145-3
|View full text |Cite
|
Sign up to set email alerts
|

Selenium environmental cycling and bioavailability: a structural chemist point of view

Abstract: International audienceSelenium is usually known as the ‘double-edged sword element' for its dual toxic and beneficial character to health. Since the pioneer works by Schwarz and Foltz on the relationships between selenium deficiency and liver, muscle and heart diseases, many efforts have been undertaken to better understand the role of selenium in health. At the same time, an increasing number of publications have appeared during these last years on the selenium physico–chemical interactions within the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
246
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(251 citation statements)
references
References 224 publications
(307 reference statements)
5
246
0
Order By: Relevance
“…Since no unmatched peaks occurred within 90 min in anion chromatography, other anionic species of Se, S or As were excluded as present in significant concentrations. The fraction of unidentified species is most likely explained by dissolved gaseous species or by (overall) neutral or cationic species (for example, complexes with organic matter, colloidal Se 33 , S or As 34 , or elemental Se, which is thermodynamically the most stable species in water at slightly acidic and redox neutral conditions 33 ). Although combined As-S or Se-S species have been observed in natural waters (for example, thio-arsenates in geothermal waters 35 , or DMSeS in marine waters 31 ), the absence of corresponding peaks for Se, S or As indicates that such species were not significantly present in the surface water samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since no unmatched peaks occurred within 90 min in anion chromatography, other anionic species of Se, S or As were excluded as present in significant concentrations. The fraction of unidentified species is most likely explained by dissolved gaseous species or by (overall) neutral or cationic species (for example, complexes with organic matter, colloidal Se 33 , S or As 34 , or elemental Se, which is thermodynamically the most stable species in water at slightly acidic and redox neutral conditions 33 ). Although combined As-S or Se-S species have been observed in natural waters (for example, thio-arsenates in geothermal waters 35 , or DMSeS in marine waters 31 ), the absence of corresponding peaks for Se, S or As indicates that such species were not significantly present in the surface water samples.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that trapped Se and S concentrations are positively correlated ( Supplementary Fig. 2), although S is volatilized to a much higher extent than Se on an absolute scale (on average up to a factor 335), might indicate that Se is volatilized by the same enzymatic system(s) as S due the chemical similarities between these elements 13,33 . For instance, thioether S-methyltransferase (EC 2.1.1.96) catalyses the methyl group transfer on DMSe and DMS with similar affinities (K m 1 and 0.4 mM, respectively) 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The high concentrations of dissolved Al and Fe in the acid leachates indicate that some soil compounds containing Al, and to a lesser extent Fe, are unstable at low pH. In previous works, Fe oxides are recognized as the main carrier phase of Se in non-volcanic soils (Dhillon and Dhillon, 1999;Fernández-Martínez and Charlet, 2009). However, our results (Fig.…”
Section: Role Of Fe and Al Phasesmentioning
confidence: 89%
“…6-15 mg/kg in Hawaii compared to 0.4 mg/kg as worldwide average), but in contrast show low Se mobility (Byers et al, 1938;John et al, 1975;Nakamaru et al, 2005). This low mobility is believed to originate from adsorption on Fe and Al minerals (John et al, 1975;Nakamaru et al, 2005), which have been widely reported as potential adsorption phases for Se (Balistrieri and Chao, 1990;Dynes and Huang, 1997;Parida et al, 1997;Wijnja and Schulthess, 2000;Duc et al, 2003;Peak et al, 2006;Fernández-Martínez and Charlet, 2009). Although soils play a key role in determining the level in food and water and thereby human health, the knowledge about the processes affecting the Se mobility in volcanic soils is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This association is possibly due to either selenium-metal-organic matter complexation, such as Se-Fe(III)-organic matter complexes, or due to biotic formation via microbial reduction of Se and further incorporation into soil organic matter structure (Gustafsson and Johnsson, 1994;Fernández-Martínez and Charlet, 2009). Most studies indicated that the association relies more on biotic formation than on abiotic complexation (Fernández-Martínez and Charlet, 2009). …”
Section: Soil Types Peat Sand Marine Clay Fluvial Clay Loessmentioning
confidence: 99%